2020
DOI: 10.4274/tjps.galenos.2019.05658
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining Stem Cell Spheroids from Foreskin Tissue and the Effect of <i>Corchorus olitorius</i> L. on Spheroid Proliferation

Abstract: Mezenkimal kök hücreler kendi kendini yenileyebilme özelliğine sahiptir. Sünnet derisinin kök hücre kaynağı olarak kullanılma potansiyeli vardır. Çalışmanın amacı, yeni doğmuş insan sünnet derisi izole hücrelerinden (hnFSSCs) sferoid oluşumunu elde etmektir. Buna ek olarak, Kıbrıs'a özgü geleneksel bir bitki olan Corchorus olitorius L. (C. olitorius) bitkisinin hnFSSCs sferoidleri üzerindeki apoptotik ve proliferatif etkileri de araştırılmıştır. Gereç ve Yöntemler: Rutin sünnet prosedüründen sonra hücreler izo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It also acts as an important pathogenic/diagnostic model of microorganisms and as a model for the examination of medications [24]. Several studies revealed that human foreskin cells could generate stem cells for tissue repair and renewal, and for the treatment of diseases [11,25,26]. Willingness to donate tissue for research has been examined by several studies from different parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…It also acts as an important pathogenic/diagnostic model of microorganisms and as a model for the examination of medications [24]. Several studies revealed that human foreskin cells could generate stem cells for tissue repair and renewal, and for the treatment of diseases [11,25,26]. Willingness to donate tissue for research has been examined by several studies from different parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…The extract was evaporated and lyophilized (Christ Alpha 1-4 LD Plus, Germany) and the final yield of crude extract was found to be 14.8 grams. Extraction composition, LC-MS/MS analysis was done by Becer et al (2020).…”
Section: Extractionmentioning
confidence: 99%